Psychological Stamina and Thinking Style Preferences among First-Year University Students (Journal of Student Affairs in Africa, 2022)
This study investigated the association between psychological stamina (grit, mindset and hardiness) and thinking style preferences among South African university students. Data were collected from 369 first-year university students using measures of grit, mindset, hardiness and thinking style preferences. The results indicated that different thinking style preferences were related to grit, mindset and hardiness. We argue that thinking styles should be considered as an important variable when supporting first-year students. Additionally, the role of grit and hardiness in student success should be considered in conjunction with the thinking style preferences of students. Avenues for further research are considered.
Keywords: grit; hardiness; mindset; Neethling Brain Instrument (NBI); thinking style preferences